DEMOGRAPHIC BONUS IN EAST JAVA: BLESSING OR DISASTER? - Iis Dwi Permatasari (East Java Economic Journal, 2018)
Demographic bonus is a phenomenon that occurs in every developing country including Indonesia. In Indonesia this phenomenon could be backfire if thegovernment can not exploit this phenomenon with the right policy. The United Nations states that demographic bonuses in Indonesia will peak in the period of 2020-2030. This paper shows the effect of demographic bonus on Gross Regional Domestic Product (GRDP) by using panel data. The regency/municipality being the sample in this research is Surabaya. Banyuwangi, Tuban, Probolinggo, Blitar, Lamongan with vulnerable time from 2010-2015. The method used in this research is by using Panel Error Correction (PEC), Vector Autoregressive (VAR) and Autoregressive Integrated Moving Average (ARIMA). The results of this study indicate that in the short and long run demographic bonus have a significant effect on East Java GRDP. Furthemore, the policy on demographic bonus is not optimal in supporting the increase of East Java GRDP. Finally, calculations using ARIMA indicate a decrease in GRDP in the next few years.